2022
DOI: 10.1016/j.ctro.2021.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Whole Brain Irradiation or Stereotactic RadioSurgery for five or more brain metastases (WHOBI-STER): A prospective comparative study of neurocognitive outcomes, level of autonomy in daily activities and quality of life

Abstract: To evaluate neurocognitive performance, daily activity and quality of life (QoL), other than usual oncologic outcomes, among patients with brain metastasis ≥5 (MBM) from solid tumors treated with Stereotactic Brain Irradiation (SBI) or Whole Brain Irradiation (WBI). Methods: This multicentric randomized controlled trial will involve the enrollment of 100 patients (50 for each arm) with MBM ≥ 5, age ≥ 18 years, Karnofsky Performance Status (KPS) ≥ 70, life expectancy > 3 months, known primary tumor, with contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…Our study also enrolled patients who received craniocerebral radiotherapy after EGFR-TKI resistance; however, this did not change the results which stated that the iPFS, PFS, and OS of the combined treatment regimen group were longer than those of the EGFR-TKI alone group. Combining the results of previous studies with our results (including the BRAIN clinical trial), we can suggest that patients with better clinical conditions and good prognosis can be treated with EGFR-TKI alone first, which can reduce the long-term adverse events caused by craniocerebral radiotherapy and improve the quality of life of patients ( 16 , 40 ). For these patients, the progression of brain metastases after EGFR-TKI treatment can be treated with craniocerebral radiotherapy to obtain longer craniocerebral local control and improve the survival prognosis of the patients.…”
Section: Discussionsupporting
confidence: 66%
“…Our study also enrolled patients who received craniocerebral radiotherapy after EGFR-TKI resistance; however, this did not change the results which stated that the iPFS, PFS, and OS of the combined treatment regimen group were longer than those of the EGFR-TKI alone group. Combining the results of previous studies with our results (including the BRAIN clinical trial), we can suggest that patients with better clinical conditions and good prognosis can be treated with EGFR-TKI alone first, which can reduce the long-term adverse events caused by craniocerebral radiotherapy and improve the quality of life of patients ( 16 , 40 ). For these patients, the progression of brain metastases after EGFR-TKI treatment can be treated with craniocerebral radiotherapy to obtain longer craniocerebral local control and improve the survival prognosis of the patients.…”
Section: Discussionsupporting
confidence: 66%
“…Indeed, nervous tissues have limited regenerative capability in response to radiation damage compared to other tissues (i.e., mucous membranes and skin) [5,6]; this is of particular concern among radiation oncologists, who must ponder every day the need for an escalated dose, such as that used in stereotactic ablative treatments, with the risk of serious adverse events (i.e., radionecrosis) [7]. In recent decades, this preliminary assessment has become particularly pervasive among insiders, since the recent advances in systemic therapy have prolonged the survival of cancer patients, making the scenario of controlled or controllable intracranial disease more common in radiotherapy departments [8]. Such a key point is of fundamental importance not only in the cerebral region but also in other neuroaxis-related sites; for example, any damage to the vertebral column could be life-altering.…”
mentioning
confidence: 99%
“…While the first is exclusively devoted to the treatment of brain targets [12], the second is also used for treating extracranial tumors [13]. In recent years, a LINAC-based RT technique-namely Volumetric Modulated Arc Therapy (VMAT), which was typically employed for limiting radiationrelated adverse events in extracranial sites [14,15]-has been enhanced with advanced Treatment Planning Systems (TPS) to plan a simultaneous radiation dose delivery to multiple brain metastases with maximal sparing of healthy tissue, similarly to what is achievable with GK [8]. Regarding the therapeutic index, these two stereotactic techniques constantly confront dosimetric challenges, and no clinical study has yet confirmed a clear benefit of the one over the other [16].…”
mentioning
confidence: 99%
“…Newer SRT protocols and patient-tailored dose planning seem to correlate with improved functional outcomes and LC, 16,29,33 similarly to other lesions benefitting from a stereotactic approach. [37][38][39] In this review, we found that spine metastatic HCCs show favorable postradiotherapy clinical and radiological responses, with acceptable complication rates.…”
Section: Discussionmentioning
confidence: 91%